Analysis of Management Overconfidence on Earnings Management in Non-Financial Companies Listed on the IDX - Duryana; Yusri Karmila (Formosa Journal of Applied Sciences, 2023)
The aim of this study is how to analyze management overconfidence in earnings management in IDX-registered non-financial companies from 2016 to 2020. Revenue management Non-financial companies BUMN on 'IDX for the period 2016-2020 can be concluded that 2016 is volatile to 2020. This means that non-financial public enterprises will have improvements in their performance. annual profit management to minimize the risk of occurrence. Managers' overconfidence in non-financial EIB companies BUMN During the period 2016-2020, there were 11 companies with excessive confidence in the performance of managers, namely INAF, KAEF, KRAS, ADHI, WIKA, WSKT, ANTM, TINS, SMBR, GIAA, TLKM, while the other 5 companies showing low confidence are PGAS, PTPP, PTBA, SMGR, JSMR.